1997
DOI: 10.1246/cl.1997.571
|View full text |Cite
|
Sign up to set email alerts
|

5,8,17,20-Tetrakis(3,5-di-t-butylphenyl)-6,7,18,19-tetradehydrotetrathia[24]annulene-(4.0.4.0) and Its Dianion: New Thiophene-Derived Paratropic and Diatropic Annulenes

Abstract: 5,8,17,20-Tetrakis(3,5-di-t-butylphenyl)-6,7,18,19-tetradehydrotetrathia[24]annulene (4.0.4.0) shows clear paratropicity (antiaromaticity) and highly amphoteric redox properties, whereas the dianion obtained by its alkali metal reduction strong diatropicity (aromaticity) as a novel 26π-electron system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The sp‐hybridized carbon atoms of intermediate 7 gave a 13 C NMR signal at δ =84.4 ppm, that is, in the δ =70–95 ppm range typical for acetylene. Similarly, the 13 C NMR chemical shifts of cumulene fragments vary over quite a wide range: δ =140.5 ppm for tetra(2‐thienyl)butatriene,11 δ =152.0 ppm for tetraphenylbutatriene,12 and δ =134.5 ppm for 6,7,18,19‐tetradehydrotetrathia[24]annulene(4.0.4.0) (some admixture of the acetylenic structure was suggested for the latter structure) 13. Thus the 13 C NMR chemical shifts of 3 point out that canonical structure 3 ac and 3 cum (ac=acetylene; cum=cumulene) contribute to the overall electronic structure, although the acetylene character of the C sp –C sp moiety prevails.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sp‐hybridized carbon atoms of intermediate 7 gave a 13 C NMR signal at δ =84.4 ppm, that is, in the δ =70–95 ppm range typical for acetylene. Similarly, the 13 C NMR chemical shifts of cumulene fragments vary over quite a wide range: δ =140.5 ppm for tetra(2‐thienyl)butatriene,11 δ =152.0 ppm for tetraphenylbutatriene,12 and δ =134.5 ppm for 6,7,18,19‐tetradehydrotetrathia[24]annulene(4.0.4.0) (some admixture of the acetylenic structure was suggested for the latter structure) 13. Thus the 13 C NMR chemical shifts of 3 point out that canonical structure 3 ac and 3 cum (ac=acetylene; cum=cumulene) contribute to the overall electronic structure, although the acetylene character of the C sp –C sp moiety prevails.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of 3 was determined by X‐ray diffraction studies and is shown in Figure 3 17. The S⋅⋅⋅S distance is short (3.113(3) Å), and only a small number of compounds that contain such close sulfur–sulfur contacts have been reported 13. 1820 The C sp 2‐C sp ‐C sp ‐C sp 2 butyne moiety reveals a slight distortion from linearity, showing a bowlike deformation directed outward of the macrocycle (C18‐C1‐C2: 174.0(9)°; C1‐C2‐C3: 176.6(9)°).…”
Section: Methodsmentioning
confidence: 99%
“…The macrocycle showed clear paratropicity (antiaromaticity) whereas the dianion, a 26π electron system which is obtained by alkali reduction, was strongly diatropic (aromatic). 670 Macrocyclization Via McMurry coupling was very recently used by Iyoda et al to synthesize large thienylene-ethynylene-vinylene macrocycles 4.54 in a statistical approach. 671 Reaction of a longer oligo(thienylene-ethynylene) dialdehyde, which was made from thiophene in 12 steps, with TiCl 4 and zinc resulted in a statistical distribution of macrocycles with various sizes (Scheme 4.19).…”
Section: Mixed Macrocycles Including R-substitution In Thiophene Unitsmentioning
confidence: 99%
“…Incorporation of an acetylene–cumulene unit into a porphyrinoid skeleton provides the unique means to design a molecular frame affording eventually effective control of the electronic structure that encloses the π-conjugation pathway of aromatic molecules. Originally, the annulene–cumulene moieties have been successfully embedded into porphyrinoids, heteroporphyrinoids, or expanded porphyrinoids, furnishing the specific subgroup of expanded porphyrinoids, the representative examples of which include acetylene–cumulene porphycene 1 (Chart ) …”
Section: Introductionmentioning
confidence: 99%